Three cycles selection among and within half sib progenies in the maize population CMS-52 - Carvalho, Hélio Wilson Lemos de; Leal, Maria de Lourdes da Silva; Guimarães, Paulo Evaristo de Oliveira; Santos, Manoel Xavier dos; Carvalho, Paulo César Lemos de (Pesquisa Agropecuaria Brasileira, 2000)
Three cycles of selection among and within half-sib progenies were carried out in the high quality protein maize (Zea mays L.) population CMS-52, at the tabuleiros costeiros of Sergipe and Bahia, Brazil, during the period of 1995 to 1997. The work aimed at obtaining a better adapted population for the regional environment. The progenies were evaluated on a 14 x 14 látice design. Recombination of the superior progenies was processed within the same year in order to get one cycle per year. The values of the genetic parameters decreased from the original cycle to cycle I, keeping at cycle II similar magnitudes of cycle I. The high magnitudes of the genetic parameters, the high productivity means of progenies, and the averaged gain expected from the selection among and within progenies per selection cycle (12.3%) show the high potential of the population to respond to selection, which will permit to attain a higher yielding population, better adapted to the regional environment. The high progeny x location interaction showed the importance for progeny evaluation in more than one location, to increase the efficiency of the selection process and to obtain more accurate estimates of variance components.